2022
DOI: 10.1002/efd2.3
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the biosynthesis, structure–activity relationships, formulations, pharmacology, and clinical trials of fisetin

Abstract: Fisetin is one of the most popular flavonoids found in vegetables and fruits with several health benefits such as antidiabetic, anticancer, and anti-inflammatory activities. Biotechnology or chemosynthesis tools were used for the synthesis of fisetin and its analogs to improve their yield and efficacy. Structure activity relationships (SARs) revealed that the aromatic hydroxyl groups especially the 3,4-dihydroxylation at ring B were crucial for fisetin biological activities, whereas substitution of several hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 123 publications
0
17
0
Order By: Relevance
“…zinc sulfate and zinc nitrate), with extremely low bioavailability and severe side effects on the gastrointestinal tract; 2) improved inorganic zinc salts (zinc gluconate and zinc citrate), with improved bioavailability and decreased severe side effects, but still affecting gastrointestinal digestion; 3) biological zinc, with significant bioavailability and no toxicity and hazards, including polysaccharide chelated zinc, protein chelated zinc, polypeptide chelated zinc ( Caetano-Silva, Netto, Bertoldo-Pacheco, Alegría, & Cilla, 2021 ). Compared with inorganic zinc, many natural substances may have the potential to be used ( Zhong, Farag, Chen, He, & Xiao, 2022 ), natural polysaccharide-zinc complex has significant advantages as a biological zinc supplement. Prepared Athelia rolfsii exopolysaccharide-zinc complexes were more effective than inorganic and organic zinc supplements in treating zinc deficiency and improving antioxidant activities in vivo ( Dong, Li, & Min, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…zinc sulfate and zinc nitrate), with extremely low bioavailability and severe side effects on the gastrointestinal tract; 2) improved inorganic zinc salts (zinc gluconate and zinc citrate), with improved bioavailability and decreased severe side effects, but still affecting gastrointestinal digestion; 3) biological zinc, with significant bioavailability and no toxicity and hazards, including polysaccharide chelated zinc, protein chelated zinc, polypeptide chelated zinc ( Caetano-Silva, Netto, Bertoldo-Pacheco, Alegría, & Cilla, 2021 ). Compared with inorganic zinc, many natural substances may have the potential to be used ( Zhong, Farag, Chen, He, & Xiao, 2022 ), natural polysaccharide-zinc complex has significant advantages as a biological zinc supplement. Prepared Athelia rolfsii exopolysaccharide-zinc complexes were more effective than inorganic and organic zinc supplements in treating zinc deficiency and improving antioxidant activities in vivo ( Dong, Li, & Min, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The contents of other fractions were low, ranging from 0.27 to 85.46 μg/g dry weight. As common bioactive polyphenols, these compounds are widely found in fruits and vegetables ( Liu et al, 2019 , Zhong et al, 2022 ). Previous studies demonstrated that polyphenols could offer good protection of oils against oxidative degradation during frying and storage ( Li et al, 2021 , Wu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 ). The structure-activity relationship (SAR) could reveal the antioxidant characteristics of these structurally related flavonols ( Zhong et al, 2022 ). The anti-oxidant potencies of dietary flavonoids are reported to be closely associated with the site and number of hydroxylations on the A and B rings.…”
Section: Discussionmentioning
confidence: 99%